Invariant optical soliton solutions to the Coupled-Higgs equation - Atas, Sibel S.; Ali, Karmina K.; Sulaiman, Tukur Abdulkadir; Bulut, Hsan (Springer, 2022)
In the present study, through the generalized exponential rational function method (GERFM), we construct optical soliton solution to the coupled-Higgs equation (CHE). The proposed method is one of the most powerful method to construct abundant exact solutions for nonlinear partial differential equations. The obtained wave solutions include hyperbolic, trigonometry, and exponential functions solutions. Furthermore, we draw three-dimensional surfaces and counter plots of the obtained solutions using the appropriate value for involved parameters.
Keywords: The system of coupled-Higgs equation; GERFM; Hyperbolic; Trigonometry; Exponential functions solutions